Pisces, Anguilliformes, Moringuidae, Moringua edwardsi (Jordan and Bollman, 1889): First record in Atol das Rocas, northeastern Brazil - Paiva, C. C.; Silva, M. B.; Lotufo, T. M. C. (Check List, 2010)
Moringua edwardsi is recorded for the first time at Atol das Rocas, northeastern Brazil. Previous records of thespecies were located in the western Atlantic Ocean, from Florida to southeastern Brazil, but with many gaps between theseregions. A single specimen was collected in Atol das Rocas in July 2007 and it is deposited in the Dias da Rocha IchthyologicalCollection. The new record of M. edwardsi fills a geographic distribution gap of this species and complements the inventoryof fish species inhabiting one of the most unique marine protected areas in the world.